Shrinkage cracking of unsaturated fine soils: New experimental device and measurement techniques. (25th April 2020) - El Hajjar, Ahmad; Ouahbi, Tariq; Eid, Joanna; Hattab, Mahdia; Taibi, Said
Abstract: Clay fine soils are characterised by an ability to change volume when subjected to suction. Soil cracking due to desiccation is a phenomenon of great importance in the environmental geotechnical engineering domain. Aiming to understand shrinkage mechanism, and conditions that lead to appearance of drying cracks, a new experimental testing coupled device digital image correlation‐ clay ring test (DIC‐CRT) was developed to investigate fine soils shrinkage and cracking. The new feature of this paper is to link both measurement techniques, based on 2D/3D‐DIC and an innovative CRT, in order to assess stress and strain in soils during desiccation. Tests were carried out on a kaolinite having a liquid limit of wL = 40%, and prepared as a slurry with w = 1.5 wL of water content. The results highlight the relevance in combining these two techniques, particularly to assess internal stresses developed in the material using CRT and link them to strains leading to cracking measured by DIC method.